Pangenome analyses reveal impact of transposable elements and ploidy on the evolution of potato species - Bozan, I.; Achakkagari, S.R.; Anglin, Noelle L.; Ellis, David; Tai, H.H.; Stromvik, M.V. (National Academy of Sciences, 2023)
Potato (Solanum sp., family Solanaceae) is the most important noncereal food crop globally. It has over 100 wild relatives in the Solanum section Petota, which features species with both sexual and asexual reproduction and varying ploidy levels. A pangenome of Solanum section Petota composed of 296 accessions was constructed including diploids and polyploids compared via presence/absence variation (PAV). The Petota core (genes shared by at least 97% of the accessions) and shell genomes (shared by 3 to 97%) are enriched in basic molecular and cellular functions, while the cloud genome (genes present in less than 3% of the member accessions) showed enrichment in transposable elements (TEs). Comparison of PAV in domesticated vs. wild accessions was made, and a phylogenetic tree was constructed based on PAVs, grouping accessions into different clades, similar to previous phylogenies produced using DNA markers. A cladewise pangenome approach identified abiotic stress response among the core genes in clade 1+2 and clade 3, and flowering/tuberization among the core genes in clade 4. The TE content differed between the clades, with clade 1+2, which is composed of species from North and Central America with reproductive isolation from species in other clades, having much lower TE content compared to other clades. In contrast, accessions with in vitro propagation history were identified and found to have high levels of TEs. Results indicate a role for TEs in adaptation to new environments, both natural and artificial, for Solanum section Petota.